Lexical, Syntactic, and Terminological Errors in Arabic-English Legal Translation among Undergraduate Students - Mowafg Abrahem; Abdulrauf Atia; Laylay Hasan; Karima Elhaj; Entisar Alatrish; Safa Alrumayh; Zaynab Omar (Saniya Institute, 2025)
This study examines the main error patterns found in Arabic-English legal translation among undergraduate students at the Faculty of Languages and Translation, University of Zawia, Libya. It seeks to identify the most frequent lexical, syntactic, and terminological errors in students’ translations and to explain these errors in relation to legal translation competence and teaching needs. The study used a corpus-based descriptive error-analysis design. Sixty undergraduate students enrolled in legal translation courses participated in the study. Each student translated a selected legal text from Arabic into English under controlled classroom conditions, and the translated scripts were compiled into a learner corpus for analysis. The findings showed a total of 538 errors across three main categories: terminological, syntactic, and lexical. Terminological errors were the most frequent, representing 45.2% of all errors, followed by syntactic errors at 31.8%, while lexical errors accounted for 23.0%. The results showed that students had the greatest difficulty in rendering specialized legal concepts accurately, maintaining terminological consistency, and distinguishing technical legal meanings from ordinary vocabulary. Syntactic difficulties also appeared in sentence structure, word order, passive voice, and the handling of complex legal clauses. The study concludes that students’ problems in legal translation may stem from limited exposure to authentic legal discourse, insufficient training in legal terminology, and overreliance on general translation strategies. The findings underline the need for more specialized, genre-based, and terminology-focused legal translation instruction in Libyan higher education.